Rupturing illusionism: the bullet catch. Issue 2 (3rd April 2018) - Rein, Katharina
ABSTRACT: In the Golden Age of stage conjuring, magicians performed various illusions 'which dismembered, disappeared or distorted human bodies'. A famous example is the notorious 'bullet catch'. The fact that a number of magicians were injured or killed performing it has become part of the publicity and mythology surrounding this illusion. Considering its inherent danger, spectators of the 'bullet catch' not only watch the staging of a shooting, respectively suicide, they are further implicitly aware of the persisting potentiality of witnessing a life-threatening or lethal accident during the show, such as the one that famously killed pseudo-Chinese magician Chung Ling Soo in 1918. Therefore, regarding illusions inspired by daredevilry and danger, the line between illusionism and reality is particularly thin. A simple false movement in a card trick will reveal the operations underlying the effect, just as a mishap during a grand illusion will bare (part of) the concealed mechanism working it. In these cases, glitches constitute a disruption of the performance's illusory character by realism. When a magician fails to catch a bullet, however, a hole in the veil of illusionism constitutes an incursion of the real that creates a drastic and violent emergency situation. With this in mind, what does the bullet catch reveal about the character of stage magic, specifically about illusions implying danger? In what way are these staged? After giving an overview of accidents and shootings in the Golden Age, this article analyzes the bullet catch in view of these questions and topoi.